Paroles d’enfants, paroles sur l’enfant atteint de cancer en hospitalisation pédiatrique à domicile - Sarra Mougel (Anthropologie & Santé)
Among the multitude of care places in which children with cancer spend time, the home has remained little studied. A prolonged observational ethnographic survey in a pediatric home care unit allowed us to reconstruct this part of children’s care trajectories. The study allows us to grasp children’s words, which are more substantial than in the hospital setting, and yet sometimes overwhelmed by the urgency of exchanges between adults. It also provides a view of the children’s agency, initiated by adults or won over by the children themselves. This agency, insofar as it is perceived by adults, can become a source of valorization for children, on the condition that it does not call into question a principle of acceptance of care. Nevertheless, the children may remain mute on the more intimate experience of their illness, as they are expected to behave like a child and not like a sick child.